Enhancement on employee’s drive and training and development results through gamification in India - Chaurasiya, Sneha (YAYASAN MITRA PERSADA NUSANTARA, 2024)
This study aims to investigate how a business enterprise uses gamification to improve the learning and development of its employees. It also discusses how gamification impacts employees’ productivity and levels of job satisfaction including job engagement level. Employing exploratory research to identify the factors that affect employee productivity, including gamification, learning and development, and others. Non-probability sampling is done. Authoritative and convenient sampling techniques of non-probability sampling have been used. Primary data of a sample population of 75 employees is collected using an online questionnaire. The findings offer practical insights for policy makers, the business enterprise the dynamic demand, training and development of the employees, paves the way for giving feedback and correction instantly, improves the team building quality and helps in team-building, develops problem solving skills and increases the confidence level along with making the employee think out of box in situations as well as develops coordination of employee increases.